FORMATION OF MILITARY JOURNALISM DURING THE SOVIET PERIOD - Nametova daughter of Bahora Botirali (Galaxy International Interdisciplinary Research Journal, 2024)
The Second World War was a responsible period for the development of military journalism and its full expression of content. Doctor of History, Professor N. Abduazizova writes, "During the 1941-1945 war, the press network, like all fronts, was somewhat reduced, the size and number of copies of a number of newspapers and magazines decreased. During this period, a military periodical press was also established in Uzbek in the territory of the former union, where military operations were taking place. During these war years, a total of 14 military newspapers were published in Uzbek."